Can the Customer Satisfaction Mediate the Relationship between Service Innovation on Revisit Intention?: A Study on Hotel Industry - Danurdara, Ananta Budhi (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of service innovation on revisit intention through customer satisfaction as an intervening variable. This research was conducted at the RedDoorz hotel located in Bandung Indonesia. The sample of this research was the hotel visitors at RedDoorz hotel. A total of 261 questionnaires were distributed, and 207 were returned. So that the sample in this study was as many as 207 respondents. The data analysis technique used is structural equation modeling. The results show that there is a positive and significant effect between service innovation on revisit intention, there is a positive and significant influence between service innovation and customer satisfaction, there is a positive and significant influence between customer satisfaction and revisit intention. Customer satisfaction mediates the relationship between service innovation and revisits intention positively and significantly.